The Foreign Policy Mechanism of the Union Of South Africa and the Development of its Diplomatic Relations (1910–1948) - ARKHANGELSKAYA Alexandra Alexandrovna (Ученые записки Института Африки Российской академии наук)
The history of the formation of South Africa as a single state is closely intertwined with events of international scale, which have accordingly influenced the definition and development of the main characteristics of the foreign policy of the emerging state. The Anglo-Boer wars and a number of other political and economic events led to the creation of the Union of South Africa under the protectorate of the British Empire in 1910. The political and economic evolution of the Union of South Africa has some specific features arising from specific historical conditions.